Knowledge of healthcare professionals of basic care about Integrative and Complementary Practices in SUS: an integrative review (Research, Society and Development, 2020)
The Integrative and Complementary Practices (PICs) are therapies that treat the individual integrally considering the interaction between user-professional, preventive practices and self-care, where the patient happens to be an active agent in the healing process. However, the provision of these services only by specialized services, scarce knowledge on the part of users, municipal managers and health professionals are some of the limiting factors for the expansion of PICs, especially in Primary Care. In this sense, the objective of this research was to analyze the scientific production referring to the knowledge of health professionals of Primary Care on PICs in SUS. This is an integrative review of the literature of articles published between 2010 and 2018, through the association of descriptors: Integrative and Complementary Practices, knowledge, health professionals and Primary Care in the following databases: LILACS, MEDLINE and SciELO. Forty-seven articles were analyzed, of which 12 were included in this review. Eleven studies were published in Portuguese (91.7%). Three studies (25%) were performed with nurses, another three with the whole FHS team (25%). Phytotherapy was studied in eight articles (66.7%). The professionals' knowledge about PICs is limited, usually related to popular knowledge, and most of the time they knew only phytotherapy and medicinal plants. results of this review demonstrated that most Primary Care health professionals are not aware of or have very limited knowledge about Integrative and Complementary Practices.